Examination of Spatial Use of Natural Potentials and Territorial Cohesion - Orosz, György (JOURNAL OF LANDSCAPE ECOLOGY, 2022)
Attila Barczi was my teacher, then my colleague and my doctoral supervisor. During the years of research, we consulted countless times, matched our own fields of expertise, sought common ground, argued and developed our common denominator. My PhD research started from the basic premise that landscape and natural indicators do not participate in the system that determines and compares the development of regions and settlements. Most of our areas with a valuable natural environment are at a disadvantage in terms of their economic and social status. Our research focused on how these areas use the opportunities provided by the natural environment in their development? What developments are planned and how do they relate to the ecosystem services provided by their natural environment? Among the research results, we have been able to describe an applicable method for strengthening the role of the natural environment for the analysis of territorial cohesion, using data that are freely available to us.
Keywords: Attila Barczi; territorial cohesion; settlement development; measurement of regional development; natural capital; ecosystem services; complex indicator